Minimalist revision of Mesochorus Gravenhorst, 1829 (Hymenoptera: Ichneumonidae: Mesochorinae) from Área de Conservación Guanacaste, Costa Rica, with 158 new species and host records for 129 species - Whitfield, Jim (2023)
Introduction: Species of Mesochorus are found worldwide and members of this genus are primarily hyperparasitoids of Ichneumonoidea and Tachinidae.  Objectives: To describe species of Costa Rican Mesochorus reared from caterpillars and to a lesser extent Malaise-trapped.  Methods: The species are diagnosed by COI mtDNA barcodes, morphological inspection, and host data. A suite of images and host data (plant, caterpillar, and primary parasitoid) are provided for each species. Results: A total of 158 new species of Mesochorus. Sharkey is the taxonomic authority for all.  Conclusions: This demonstrates a practical application of DNA barcoding that can be applied to the masses of undescribed neotropical insect species in hyperdiverse groups.